A Multistep Validation Procedure for Monitoring Compliance of a Large Network of Connected Hospital Glucose Meters to International Quality and Performance Standards. Issue 2 (June 2020) - Blairon, Laurent; Wilmet, Alain; Beukinga, Ingrid; Tré-Hardy, Marie
Abstract : Abstract: The ISO 22870:2016 standard requires validation of point-of-care testing (POCT) instruments before routine use. Although it is a relatively easy task for blood gas analyzers, it is much more involved in connected blood glucose monitoring (BGM) devices because they are used ubiquitously and in large numbers throughout hospital departments. Here we present the model used in order to validate efficiently and effectively compliance of 116 glucose/ketone BGM devices to ISO 22870. In a first step, a "reference" BGM was established and fully evaluated in comparison to our criterion-standard laboratory method. The 115 remaining connected and hospital-wide distributed BGM devices were then correlated against the "reference" BGM. We spiked donated blood samples with increasing amounts of glucose derived from a diluted oral glucose solution and tested it with the reference StatStrip BGM device and with a cobas 8000 glucose laboratory comparison method. Every connected BGM device was then compared with the BGM reference device using the same sample preparation methodology. The ISO 15197, POCT 12-A3, and Food and Drug Administration performance acceptance criteria were used for comparing the BGM reference results with the laboratory criterion-standard results and for comparing BGM reference results with the connected hospital BGM devices. Repeatability and interassay precision were assessed with aqueous controls. We show that it is possible to validate compliance of a large number of connected POCT BGM devices to ISO 22870 efficiently and effectively using only 1 operator. The StatStrip BGM device performances were excellent and met the ISO 15197, POCT 12-A3, and Food and Drug Administration criteria.